Performance evaluation of titanium-based metal nitride coatings and die lifetime prediction in a cold extrusion process - Shen Li (De Gruyter, 2021)
Surface coating can greatly enhance the lifetime of cold extrusion die. It is a significant issue to evaluate the performance of coatings and even predict the lifetime of cold extrusion die. In this work, the titanium-based nitride coatings including TiN, TiAlN, and TiAlCrN were, respectively, deposited on the surface of high-speed steel substrate W6Mo5Cr4V2 (M2) by the physical vapor deposition technology. The hardness test, scratch test, Rockwell adhesion test, and pin-on-disc (POD) wear test were carried out aiming to investigate the performances of the three coatings including hardness, adhesion strength, and wear resistance. The results show that the TiAlCrN coating exhibits the highest hardness of 3,033 HV in comparison with TiN coating (1,222 HV) and TiAlN coating (1,916 HV), while it possesses poor adhesion strength and inferior wear resistance. Furthermore, the TiAlN coating presents the highest resistance to wear and spalling from the substrate. In addition, the Archard wear model of the coatings was solved and applied in the finite element model of cold extrusion to calculate the wear depth and lifetime of the cold extrusion dies. The results suggest that TiAlN coating is the optimal option for cold extrusion die as compared with TiAlCrN and TiN coatings. TiAlN coating can prolong the lifetime of the substrate die up to 260%.